Actuating Supramolecular Shape Memorized Hydrogel Toward Programmable Shape Deformation. Issue 48 (9th November 2020) - Lu, Huanhuan; Wu, Baoyi; Yang, Xuxu; Zhang, Jiawei; Jian, Yukun; Yan, Huizhen; Zhang, Dachuan; Xue, Qunji; Chen, Tao
Abstract: Inspired by nature, diverse biomimetic hydrogel actuators are fabricated and become one of the most essential components of bionics research. Usually, the anisotropic structure of a hydrogel actuator is generated at the early fabrication process, only a specific shape transformation behavior can be produced under external stimuli, and thus has limited the development of hydrogel actuators toward the biomimetic shape deformation behavior. Herein, a novel bilayer hydrogel having a thermoresponsive actuating layer and a metal ion‐responsive memorizing layer is proposed, therefore, a 2D hydrogel film can be fixed into various 3D shapes via supramolecular metal‐ligand coordination, with further realizing programmable 4D shape deformation under the stimulus of temperature. By manipulating the temporary shapes via shape memory behavior, various temporary anisotropic structures can be obtained via the bilayer hydrogel, thus producing diverse reversible shape deformation performances, which is expected to promote the development of intelligent polymeric materials. Abstract : A novel bilayer hydrogel with a thermoresponsive actuating layer and a metal ion‐responsive memorizing layer is presented. Taking advantage of the shape memory behavior, one initial hydrogel can be fixed into various temporary anisotropic shapes via supramolecular metal‐ligand coordination, and achieving diverse reversible shape deformation performances upon the trigger of temperature.